Improving Student Learning Outcomes Qs Material. Al-Hujurat/49:13 Through The Make a Match Method Class IV (Four) SDN 23 Tulang Bawang Tengah - Pertiwi, Leli Apriyanti; Mayasari, Ruhana; Kadi; Anam, Wahidul; Anam, Masrul (Faculty of Tarbiyah, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2023)
QS material. Al-Hujurat/ 49: 13 is an aspect of Al-Qur'an Hadith. In general, Al-Qur'an Hadith material is learned by students by listening to teacher lectures. Facing conditions like this, the author is interested in conducting classroom action research to find a way or learning technique supported by learning media so that students can be active involved and can improve their learning outcomes. Thus, the research this time the author took the title of improving the learning outcomes of fourth grade students towards understanding the material QS. Al-Hujurat/ 49: 13 through the Make a Match Method at SDN 23 Tulang Bawang Tengah. This study aims to improve student learning outcomes so as to improve student abilities and creativity by using fun learning methods (cooperative learning). The form of research used is classroom action research conducted in 2 cycles, each cycle consists of planning, action, observation and reflection. The instruments used in this research is a questionnaire of student learning outcomes. The results of this class action research is expected to have a positive impact on classroom learning, especially Islamic Religious Education subjects in the elements of Al-Qur'an Hadith, especially the material of Let's Recite and Study QS. Al-hujurat/ 49: 13.